Rectovaginal Fistula as a Complication of Fecal Management System. (August 2019) - Butts, Emily; Padala, Sandeep Anand; Vakiti, Anusha; Kota, Vamsi
We report a rare complication of the use of an intrarectal catheter. An 18-year-old female with T-cell acute lymphoblastic leukemia post-matched unrelated donor allogeneic stem cell transplantation (auto-SCT) developed hepatic encephalopathy secondary to hepatic sinusoidal obstructive disease. A fecal management system was used to contain and divert fecal matter in this immobilized patient. Approximately 1 month after placement of an intrarectal catheter, stool was noted in the vaginal vault. Speculum examination confirmed development of a rectovaginal fistula.